Progressive Multifocal Leukoencephalopathy in a HIV Negative, Immunocompetent Patient - T. Nanda (Case Reports in Neurological Medicine)
Progressive multifocal leukoencephalopathy (PML) is a rare demyelinating disease most common in immunodeficient patients. It occurs due to reactivation of the John Cunningham Virus (JCV) and carries a poor prognosis, with a median life expectancy of 6 months. We report a case of a 66-year-old man with a history of HCV related cirrhosis (HCV) and hepatocellular carcinoma (HCC) who was found to have PML in the setting of a negative viral load in the CSF and a CD4+ >200. He initially presented with two weeks of mild confusion and word-finding difficulty concerning for hepatic encephalopathy. An MRI was notable for extensive T2/FLAIR hyperintensity signal in the left temporal lobe. Brain biopsy was positive for JCV. PML is rare in immunocompetent individuals, especially in the setting of a negative viral load. It is possible, however, that transient states of immunosuppression may have been responsible in this case. Although viral load was reported as negative, virus may still have been detected but was below the quantifiable threshold. It is important for clinicians to note that a negative result does not necessarily exclude the possibility of PML, and care should be taken to review lab values on viral load in closer detail.